Cigarette Smoke Induces Intestinal Inflammation via a Th17 Cell-Neutrophil Axis - Kim, Myunghoo; Gu, Bonhee; Madison, Matthew C.; Song, Hyo Won; Norwood, Kendra; Hill, Andrea A.; Wu, Wan-Jung; Corry, David; Kheradmand, Farrah; Diehl, Gretchen E. (Frontiers in Immunology, 2019)
Epidemiological evidence finds cigarette smoking is a common risk factor for a number of diseases, not only in the lung but also in other tissues such as the gastrointestinal tract. While it is well documented that smoking directly drives lung inflammatory disease, how it promotes disease in peripheral tissues is incompletely understood. In this study, we utilized a mouse model of short-term smoke exposure and found increased Th17 cells and neutrophilia in the lung as well as in the circulation. Following intestinal inflammatory challenge, smoke exposed mice showed increased pathology which corresponds to enhanced intestinal Th17 cells, ILC3 and neutrophils within intestinal tissue. Using cellular depletion and genetic deficiencies, we define a cellular loop by which IL-17A and downstream neutrophils drive cigarette smoke-enhanced intestinal inflammation. Collectively, cigarette smoke induced local lung Th17 responses lead to increased systemic susceptibility to inflammatory insult through enhanced circulating neutrophils. These data demonstrate a cellular pathway by which inflammatory challenge in the lung can sensitize the intestine to enhanced pathological innate and adaptive immune responses.